Low Rates of Mother-to-Child HIV Transmission in a Routine Programmatic Setting in Lilongwe, Malawi - Kim, Maria H. (Public Library of Science, 2013)
BACKGROUND: The Tingathe program utilizes community health workers to improve prevention of mother-to-child transmission (PMTCT) service delivery. We evaluated the impact of antiretroviral (ARV) regimen and maternal CD4+ count on HIV transmission within the Tingathe program in Lilongwe, Malawi. METHODS: We reviewed clinical records of 1088 mother-infant pairs enrolled from March 2009 to March 2011 who completed follow-up to first DNA PCR. Eligibility for antiretroviral treatment (ART) was determined by CD4+ cell count (CD4+) for women not yet on ART. ART-eligible women initiated stavudine-lamivudine-nevirapine. Early ART was defined as ART for ≥14 weeks prior to delivery. For women ineligible for ART, optimal ARV prophylaxis was maternal AZT ≥6 weeks+sdNVP, and infant sdNVP+AZT for 1 week. HIV transmission rates were determined for ARV regimens, and factors associated with vertical transmission were identified using bivariate logistic regression. RESULTS: Transmission rate at first PCR was 4.1%. Pairs receiving suboptimal ARV prophylaxis were more likely to transmit HIV (10.3%, 95% CI, 5.5–18.1%). ART was associated with reduced transmission (1.4%, 95% CI, 0.6–3.0%), with early ART associated with decreased transmission (no transmission), compared to all other treatment groups (p = 0.001). No association was detected between transmission and CD4+ categories (p = 0.337), trimester of pregnancy at enrollment (p = 0.100), or maternal age (p = 0.164). CONCLUSION: Low rates of MTCT of HIV are possible in resource-constrained settings under routine programmatic conditions. No transmissions were observed among women on ART for more than 14 weeks prior to delivery.